Two new species of Protimesius from northern Brazil (Opiliones: Laniatores: Stygnidae) - Bragagnolo, Cibele (Zootaxa, 2013)
Two new species of Protimesius Roewer, 1913 (Stygnidae), are described from northern Brazil. Protimesius regalo sp. nov. is described from Lageado, state of Tocantins. This is a large species and can be easily distinguished from the already described species of Protimesius by the presence of four apical mesal acute tubercles on tibia IV and two dorsal rows of tubercles on male patella IV. Protimesius jirau sp. nov. is described from Porto Velho, state of Rondônia. This species is similar to P. cirio in having a large, pointed, dorso-apical apophysis on the male trochanter IV. However, it can be distinguished from P. cirio by the absence of a ventral row of tubercles on the male femur IV, as well as the presence of a ventral row of tubercles and two postero-distal apophyses on the male tibia IV. A new cladistic analysis for the genus is presented, and a key is given for the 18 species of Protimesius for which males are known.